Тяговый баланс перспективного колесного бронетранспортера с электромеханической трансмиссией - Волонцевич, Дмитрий Олегович; Веретенников, Евгений Александрович; Мормило, Яков Михайлович; Яремченко, Анатолий Сергеевич; Карпов, Вадим Олегович (НТУ "ХПИ", 2017)
Предлагается оценка мощности тягового электропривода для реализации заданных характеристик подвижности колесного бронетранспортера БТР-4 и проводится анализ возможности построения электромеханической трансмиссии для указанной машины с одноступенчатыми и двухступенчатыми колесными редукторами. Сделан вывод о невозможности обойтись без расширения диапазона изменения крутящего момента на механическом двухступенчатом колесном редукторе в случае использования тяговых электродвигателей типа EMRAX 348 (Словения).

It is proposed evaluation of the power of the traction electric drive for the implementation of the specified characteristics of the mobility of a wheeled armored personnel carrier BTR-4. The values of the required power were determined for the implementation of each requirement to mobility separately. As a result the rational value of the mechanical power output on wheels was chosen, which able to satisfy the requirements of machine mobility. Analysis of the feasibility of developing an electromechanical transmission for wheeled armored personnel carrier BTR-4 with a single-stage and two-stage wheel gearboxes was conducted. It is concluded that using traction motor EMRAX 348 (Slovenia) can not use single-stage wheel gearboxes without derating machine mobility. The value of the required coefficient adaptability for torque of the traction motor to be able to use it with single-stage wheel gearboxes was determined.
Traction balance for perspective wheeled armored personnel carrier with electromechanical transmission
Keywords: подвижность; динамические характеристики; колесные редукторы; одноступенчастые редукторы; двухступенчатые редукторы; armored personnel carrier; electromechanical transmission; mobility; dynamic performance